Two new species of terrestrial-breeding frogs (Anura: Brachycephaloidea) from Cordillera de Colán, Peru - Venegas, Pablo Javier; García-Ayachi, Luis Alberto; Ormeño, Jesús; Bullard, Santiago; Catenazzi, Alessandro; Motta, Ana Paula [UNESP] (Universidad Regional Amazónica Ikiam, 2021)
We describe two new species of terrestrial-breeding frogs from the Cordillera de Colán, in northeastern Peru. We used Parsimony and Maximum Likelihood approaches to infer a molecular phylogeny on a dataset composed of 75 terminals, including three terminals representing the new species, and 4202 bp of concatenated mtDNA and nuDNA fragments. Our phylogenetic analyses support the placement of the two new species in Lynchius and Oreobates, respectively. The new species of Lynchius occurs in two localities from 1,977 to 2,006 m a.s.l., and is characterized by having a dorsum covered by conical tubercles and a brown dorsal coloration lacking a pattern of blotches on the hidden surfaces of flanks and hindlimbs. The new species of Oreobates is only known from one location at 2608 m a.s.l. and is characterized by the absence of axillary and inguinal glands, and the presence of white or cream blotches on the dark brown hidden surfaces of the body.
Keywords: Andes; Huancabamba depression; Lynchius; Oreobates; Río Marañón